Text entry for ultra-small touchscreens using a fixed cursor and movable keyboard. - Shibata, Tomoki.; Afergan, Daniel.; Kong, Danielle.; Yuksel, Beste F.; MacKenzie, I. Scott, 1951-; Jacob, Robert J. K. (Tufts University. Tisch Library., 2017)
Emerging ultra-small wearables like smartwatches pose a design challenge for touch-based text entry, due to the "fat finger" problem, wherein users struggle to select elements much smaller than their fingers. In order to address the challenge, we introduce DriftBoard, a panning-based text entry technique in which the user types by navigating the movable QWERTY keyboard with respect to the fixed cursor point. In this paper, we describe interactions on the proposed typing system, and report a preliminary result of our user study on a watch-size touchscreen with a text copy task comparing DriftBoard to two published ultra-small keyboards, ZoomBoard (tapping-based) and Swipeboard (swiping-based) Within the user study, DriftBoard performed comparably (no significant difference) to ZoomBoard in the major metrics of text entry speed and error rate, and outperformed Swipeboard, which suggests that the proposed panning-based typing is another promising input form for text entry on ultra-small touchscreens.